ARTIFICIAL INTELLIGENCE-ASSISTED MACHINE LEARNING METHODS FOR FORECASTING GREEN BOND INDEX: A COMPARATIVE ANALYSIS - Gur, Yunus Emre; Simsek, Ahmed Ihsan; Bulut, Emre (Economic and Financial Research Assoc - Efad, 2024)
The main objective of this study is to contribute to the literature by forecasting green bond index with different machine learning models supported by artificial intelligence. The data from 1 June 2021 to 29 April 2024, collected from many sources, was separated into training and test sets, and standard preparation was conducted for each. The model's dependent variable is the Global S&P Green Bond Index, which monitors the performance of green bonds in global financial markets and serves as a comprehensive benchmark for the study. To evaluate and compare the performance of the trained machine learning models (Random Forest, Linear Regression, Rational Quadratic Gaussian Process Regression (GPR), XGBoost, MLP, and Linear SVM), RMSE, MSE, MAE, MAPE, and R2 were used as evaluation metrics and the best performing model was Rational Quadratic GPR. The concluding segment of the SHAP analysis reveals the primary factors influencing the model's forecasts. It is evident that the model assigns considerable importance to macroeconomic indicators, including the DXY (US Dollar Index), XAU (Gold Spot Price), and MSCI (Morgan Stanley Capital International). This work is expected to enhance the literature, as studies directly comparable to this research are limited in this field.
Keywords: Green Bonds; Machine Learning; Rational Quadratic; Gaussian Process; Regression; SHAP; Analysis; Nonlinear